Telomere and telomerase: Brief review of a history initiated by Hermann Müller and Barbara McClintock (2006)
What is the nature of the biological clock that determines the cells aging? What is the way to explain the genesis of diseases associated in aging? The above are only some of the questions whose answer could be found within the modus operandi frame of the telomere-telomerase pair, which had become in objective of study for a number of science men and women since the pioneers Hermann Müller and Barbara McClintock, until the most recent Jack Szostak, Elizabeth Blackburn and Carol Greider, among others. © 2006 Corporación Editora Médica del Valle.